Coping profiles and health outcomes among individuals with systemic sclerosis: A latent profile analysis approach. Issue 3 (October 2020) - Condon, Shelley E; Roesch, Scott C; Clements, Philip J; Furst, Daniel E; Weisman, Michael H; Malcarne, Vanessa L
Background: Systemic sclerosis has negative implications for quality of life, and coping is a mechanism by which individuals can adapt more successfully to illness. This study (1) identified coping profiles in patients with systemic sclerosis and (2) examined distress and disability correlates of the profiles. Methods: A sample of 93 patients with confirmed diagnoses of systemic sclerosis received clinical examinations and reported on coping, psychological distress, and health-related disability. Latent profile analysis was used to identify coping-based profile groups. The profile groups were then compared on psychological distress and health-related disability, controlling for disease severity. Results: A two-profile solution was supported: Active Copers emphasized problem-focused, social support, counting blessings, and religious approaches to coping with systemic sclerosis. Passive Copers emphasized blaming self and others, avoidance, and wishful thinking approaches to coping. Active Copers reported significantly less psychological distress than Passive Copers, but no significant differences were found for health-related disability. Discussion: The findings identify multidimensional patterns of coping that are differentially related to psychological distress in systemic sclerosis patients. These findings can inform coping-based interventions for patients with systemic sclerosis.